Results of Experimental Studies on using MWF Electromagnetic Field Energy for Pre-Sowing Treatment of Grain Crops - Konstantin V. Kazakov, Yuri N. Ulyantsev, Sergey V. Vendin, Yury V. Saenko, Oksana V. Kitaeva, Sergey V. Solovev (International Journal of Advanced Science and Technology, 2020)
The paper presents a methodological approach to studying the processes of electrophysical influence of microwave frequency electromagnetic field on agricultural crop seeds. A classification of the options for technological implementation of MWF seeds treatment processes is given. It has been found that the most technologically appropriate methods for MWF treatment of seeds are as follows: treatment of the layer of seeds exposed to a radiator and MWF treatment of seeds flow in an in-line resonator chamber. The general methodology and results of experimental studies on pre-sowing seed treatment have also been given. The results of regression analysis of experimental data on the effect of MWF treatment modes on wheat seeds germination ability are provided. Regression equations are given, and an analysis is conducted of the effect of the specific MWF power and exposure, with regression equations of the effect of MWF heating rate and final temperature. Analysing the effect of the specific MWF power and exposure on the wheat seeds germination ability has shown that the same results of treatment can be obtained at the different values of the specific MWF power and exposure time. Hence, to obtain a positive result of treatment, it is necessary to take into consideration technical and technological capabilities and establish a “secure boundary”: specific power of exposure – time of treatment. Analysing the effect of final temperature and heating rate on germination ability of wheat seeds has shown that the factor of MWF heating rate is more significant as compared to final temperature. It is likely related to the integral temperature effect. Hence, to have a positive treatment result, technical and technological capabilities of the equipment should be taken into account, specifying one of the parameters and defining the second one according to the nomograph of the required germination ability, however, to that end, a “secure boundary”: final temperature of MWF heating – rate of MWF heating, should be established. Boundary dependence “final MWF heating temperature – MWF heating rate” will actually define the parameters of controlling the process of MWF treatment, and, hence, makes it possible to automate the process of MWF seeds treatment with monitoring by temperature factors. To do this, it is required to experimentally specify the permissible values of MWF heating rate and final heating temperature for the seeds of various crops.